Safety and efficacy of naltrexone for weight loss in adult patients – a systematic review - Kulak-Bejda, Agnieszka (Arch Med Sci, 2020)
INTRODUCTION: This is a report of a systematic review of the safety and efficacy of naltrexone or naltrexone/bupropion on weight loss. MATERIAL AND METHODS: The databases Medline, PubMed, and Embase as well as the Cochrane Controlled Trials Register for randomized controlled trials were searched for studies published from January 1966 to January 2018. A meta-analysis, randomised controlled trials, controlled trials, uncontrolled trials, cohort studies and open-label studies were analysed. RESULTS: Of 191 articles, 14 fulfilled the inclusion criteria: 1 meta-analysis, 10 randomized controlled trials, and 3 studies without randomization were found. In these studies, the efficacy and safety of naltrexone/bupropion in obesity were analysed. In the majority of these studies, patients with at least 5% or 10% weight loss, as a primary outcome, were investigated. Generally, naltrexone/bupropion treatment can be a promising therapy for obese patients, including when combined with mental health treatment. CONCLUSIONS: Based on these studies, it can be said that naltrexone/bupropion treatment is effective in the weight loss of overweight subjects. The naltrexone/bupropion treatment was well tolerated by the patients, and side effects were rarely reported.